Immuno- and expression analysis of Ehrlichia canis immunoreactive proteins - Jignesh G. Patel; Tian Luo; Xiaofeng Zhang; Jere W. McBride; Jere W. McBride; Jere W. McBride; Jere W. McBride; Jere W. McBride (Frontiers in Veterinary Science)
Ehrlichia canis is the primary etiologic agent of canine monocytic ehrlichiosis, a serious and sometimes fatal hemorrhagic disease of dogs. Diagnosis of E. canis infection is often retrospectively confirmed by serologic detection of antibodies by immunofluorescent microscopy. Our laboratory previously identified numerous major immunoreactive proteins with species-specific linear antibody epitopes that are useful for immunodiagnosis of CME. More recently, we have defined the entire antibody-reactive immunome of E. canis, substantially increasing the number of major immunoreactive proteins known to exist. In this study, we analyzed and compared seven recently identified antibody reactive E. canis proteins with established diagnostic antigens including tandem repeat proteins TRP19, TRP36 and TRP140 and observed comparable immunoreactivity. Many of these proteins were conserved in different E. canis strains. Multiple linear antibody epitopes were mapped in a highly conserved TRP (Ecaj_0126), including within the tandem repeat domain. Temporal antibody responses were examined, and multiple proteins reacted with antibodies in sera as early as 21 days post experimental infection. Host-specific expression of the proteins was examined which revealed that some proteins exhibited higher expression in mammalian cells, while others in tick cells. This study has identified new immunodiagnostic candidates that exhibit different host expression patterns, information which may be useful for developing ultrasensitive immunodiagnostics and effective vaccines for CME.